The Toxicity of Torture: The Cultural Structure of US Political Discourse of Waterboarding. - Del Rosso, Jared (Social Forces, 2014)
Drawing on a qualitative analysis of 21 hearings held by the US Congress in 2007 and 2008, this manuscript examines the discursive work that proponents and opponents of waterboarding used to maintain and challenge the legitimacy of the practice. The juxtaposition reveals that US political discourse of waterboarding orients to a long-standing cultural coding of torture as antithetical to liberal democracy. Specifically, I show that proponents defend waterboarding by narrating its use within a sequence of instrumentally rational actions that begins with the capture of a terrorist, involves the unsuccessful use of traditional interrogation techniques followed by waterboarding, and concludes with the collection of intelligence that frustrates terroristic activities. In this sequence, waterboarding appears to be a last resort in the pursuit of a legitimate state goal. Opponents of waterboarding, conversely, emphasize the practice's illiberal qualities, arguing that waterboarding produces compliant detainees who will say anything to end their torture. Opponents also describe the physical horrors associated with torture and compare waterboarding to practices employed by notorious illiberal regimes. I demonstrate that these opposing depictions of waterboarding derive their resonance from a single cultural code that legitimates instrumentally rational expressions of state violence and abhors ferocious, repressive forms. I conclude by discussing the implications of these findings for the study of torture, state violence, and human rights.